Islamic Legal Hybridity in the Mappatoi System: Sharia Economic Adaptation among Minority Muslim Communities in Plural Society - Qamaruddin, Muh. Yusuf; Salju, Salju; Harahap, Burhanuddin; Tamami, Ahmad; Isman, Ainul Fatha; Katman, Muhammad Nasri; Wan Zulkiffli, Wan Farha binti (Jurnal Ilmiah Al-Syir'ah, 2025)
This study analyzes the implementation of Islamic economic principles in the mappatoi system as a form of sharia economic adaptation among minority Muslim communities in Cendana Putih 1 Village, North Luwu, living in a plural society dominated by Hindu customary systems. The research employs a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with Muslim and Hindu farmers, and document analysis. Data analysis utilized a descriptive-qualitative approach with a fiqh al-aqalliyyat framework. Findings reveal the phenomenon of "Islamic legal hybridity in minority agrarian economics" where the mappatoi system functions as vernacular Islamic economics that maintains maqasid al-shariah through creative adaptation. The study also discovered "unconscious Islamic compliance" among Hindu participants, demonstrating convergence of universal ethical values. The research develops a theoretical framework of "Islamic Legal Hybridity" that explains how Islamic economic principles can be adapted within traditional economic systems through sophisticated value negotiation. Occupational homogeneity in the agricultural sector serves as a cross-religious bridge facilitating sustainable economic cooperation.